The Woman I Am Southern Baptist Women's Writings, 1906-2006. - Maxwell, Melody (Tuscaloosa : University of Alabama Press, 2014)
Melody Maxwell's The Woman I Am analyzes the traditional, progressive, and potential roles female Southern Baptist writers and editors portrayed for Southern Baptist women from 1906 to 2006, particularly in the area of missions.The Southern Baptist Convention (SBC) represents the largest Protestant denomination in the United States, yet Southern Baptist women's voices have been underreported in studies of American religion and culture. In The Woman I Am, Melody Maxwell explores how female Southern Baptist writers and editors in the twentieth century depicted changing roles.
Acknowledgments; Abbreviations; 1. Southern Baptist Women's Writings in Context; 2. Woman's Work for Woman, 1906-1918; 3. Supporting the SBC, 1919-1945; 4. Cultivating a Christian Influence, 1946-1967; 5. Almost Unlimited Possibilities, 1968-1983; 6. Developing Spiritually in a Context of Division, 1984-2006; 7. Southern Baptist Women's Writings in Retrospect; Appendixes; Notes; Bibliography; Index
Description based upon print version of record.
Keywords: Southern Baptist Convention -- History; Baptist women -- United States -- History -- 20th century; Christian literature -- Authorship; RELIGION / Christianity / Baptist; Electronic books